Holographic projection interferometer with photorefractive recording media - Derzhypolska, Liudmyla; Davidenko, N.; Medved, Nataliya; Priadko, Larysa (My University, 2004)
Characteristics of a holographic interferometer with photorefractive media that includes a regime of areal time registration of holograms are considered. The interferometer arranges an optical fiber bunch that allows one to use this scheme for delivery of optical information from hard accessible places. Distortions coming from changes of mode structure of the probe fiber bunch during hologram recording are decreased significantly owing to the features of the proposed optical setup and the method of registration.
Keywords: spatial and angular characteristics; interferometer; laser beams; hologram; просторово-кутові характеристики; інтерферометр; лазерні пучки; голограма; кафедра фізики та професійної безпеки